Sistematización de los procesos de monitoreo de la calidad del aire desarrollados en el cantón Latacunga. - Vásquez Camalle, Lisbeth Mireya (2022)
Every year around the world, exposure to air pollution causes 7 million premature deaths and a decrease in human life expectancy. One of the problems caused by large urban concentrations is air pollution, which has been occurring in recent years due to rapid population growth, the increase in the number of vehicles, industrial development, among other causes. The purpose of this research study was to systematize the air quality monitoring processes obtained in different studies developed in Latacunga Canton. The methodology used is based on data collection processes of research conducted between 2013 and 2020 of air quality monitoring in Latacunga Canton, where it was possible to identify 3 types of pollutants such as stationary sources, mobile sources, and particulate matter with 7, 1, and 20 monitoring points respectively. In the same way, the monitoring procedure developed for air quality was identified for each type of pollutant. The monitoring process for fixed sources was based on Annex 3 and 4 of Book VI of the TULSMA standard for air emissions from fixed sources, for the monitoring process for mobile sources it was based on the instructions of the AVL DITEST gas 1000 equipment for pollutants produced by the combustion of gasoline-powered vehicles; for the monitoring process of the concentration of particulate matter (PM10, PM2. 5) was based on the TULSMA Standard for sampling with E-BAM equipment. In the analysis of the systematization of the results, it was identified that, of the three types of pollutants, pollution from mobile sources resulting from the combustion of gasoline-powered vehicles generates the greater negative impact on air quality in Latacunga, since its parameters exceed the maximum permissible limit of the environmental standards, followed by pollution resulting from the concentration of PM10 particulate matter.